2023
DOI: 10.3389/fneur.2023.1302622
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid drainage and chronic hydrocephalus in aneurysmal subarachnoid hemorrhage patients with intraventricular hemorrhage

Botao Wu,
Yang Zhou,
Hongjun Fan
et al.

Abstract: BackgroundPatients with intraventricular hemorrhage (IVH) are at a higher risk of developing hydrocephalus and often require external ventricular drainage or long-term ventriculoperitoneal shunt surgery.ObjectiveTo investigate whether cerebrospinal fluid drainage in patients with IVH due to aneurysmal subarachnoid hemorrhage (aSAH) reduces the incidence of chronic hydrocephalus.MethodA retrospective analysis was conducted on patients with aSAH treated at our hospital between January 2020 and December 2022. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Chronic hydrocephalus has been demonstrated to be associated with the arachnoid detritus, formed by the breakdown of blood components due to leptomeningeal reactions and the volume of drained CSF ( 4 ). Although lumbar drainage could aid in blood clearance, potentially reducing chronic hydrocephalus ( 38 ), numerous studies have identified that CSF volumes exceeding 1,500 mL within the initial week of drainage ( 8 ), or high thresholds ranging from 78 to 214 mL of CSF drainage within 72 h after aSAH, serve as reliable predictors of chronic hydrocephalus ( 30 ). Consistent with our findings, lumbar drainage likely accelerates the removal of disintegrated blood products.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hydrocephalus has been demonstrated to be associated with the arachnoid detritus, formed by the breakdown of blood components due to leptomeningeal reactions and the volume of drained CSF ( 4 ). Although lumbar drainage could aid in blood clearance, potentially reducing chronic hydrocephalus ( 38 ), numerous studies have identified that CSF volumes exceeding 1,500 mL within the initial week of drainage ( 8 ), or high thresholds ranging from 78 to 214 mL of CSF drainage within 72 h after aSAH, serve as reliable predictors of chronic hydrocephalus ( 30 ). Consistent with our findings, lumbar drainage likely accelerates the removal of disintegrated blood products.…”
Section: Discussionmentioning
confidence: 99%